Evaluation of Different Attractive Traps for Capturing Sand Flies (Diptera: Psychodidae) in an Endemic Area of Leishmaniasis, Southeast of Iran - Saideh Yousefi (Journal of Arthropod-Borne Diseases, 2020)
Background: The attraction of phlebotomine sand flies to plant and animal hosts is due to the produced chemical compounds, affecting the olfactory receptors of the insects. Therefore, novel and effective methods, such as Attractive Toxic Sugar Baits (ATSB) and Attractive Toxic Baits (ATB), are based on the effective materials that attract sand flies toward the host. The present study was designed to identify the attractive materials in plants and animals for using in ATSB and ATB. Methods: This cross-sectional study was carried out in July 2018 on endemic areas of leishmaniasis in Iran. Different baits, including mango, nectarine, grape, banana, melon and watermelon, defibrinated blood of cattle, sheep, goat and chicken, urine of cattle, sheep, goat and ultimately, simple and complex chemicals, such as CO2, 1-octanol, lactic acid and human sweat were placed inside the traps, and the rate of  the sand flies attraction to these materials was studied. Furthermore, data were analyzed using the Kruskal-Wallis test and Mann Whitney U test. Results: There was a significant difference in the sand flies attraction between the traps containing watermelon, urine of cattle, and sheep, and chemicals such as CO2 and human sweat and the control trap (p< 0.05). Conclusion: This study showed that watermelon and CO2 are the potential candidates for using in ATSB and ATB, respectively.